Documents on German foreign policy: 1918-1945 : from the archives of the German foreign ministry. (United States of America. Government Printing Office, 1949)
Analytical list of documents -- Germany and the Great of Wwestern Eyrope, September 30 1937-March 1938 -- Germany and the United States-1937 -- Germany and the Far East-1938 -- Germany and the Soviet Union-1937-1938 --